Construction of a vascularized fascia-prosthesis compound model with axial pedicle for ear reconstruction surgery - Li, Guanmin; Lei, Chen; Shan, Xiuying; Ni, Xuejun; Chen, Guojie; Wang, Meishui; Ke, Ruonan; Wang, Biao (Frontiers in Bioengineering and Biotechnology, 2023)
BACKGROUND: To design a vascular pedicled fascia-prosthesis compound model that can be used for ear reconstruction surgery. METHODS: A vascularized tissue engineering chamber model was constructed in New Zealand rabbits, and fresh tissues were obtained after four weeks. The histomorphology and vascularization of the newly born tissue compound were analyzed and evaluated by tissue staining and Micro-CT scanning. RESULTS: The neoplastic fibrous tissue formed in the vascularized tissue engineering chamber with the introduction of abdominal superficial vessels, similar to normal fascia, was superior to the control group in terms of vascularization, vascular density, total vascular volume, and total vascular volume/total tissue volume. CONCLUSION: In vivo, introducing abdominal superficial vessels in the tissue engineering chamber prepped for ear prosthesis may form a well-vascularized pedicled fascia-prosthesis compound that can be used for ear reconstruction.